Using 67Cu to Study the Biogeochemical Cycling of Copper in the Northeast Subarctic Pacific Ocean - Semeniuk, David M.; Bundy, Randelle M.; Posacka, Anna M.; Robert, Marie; Barbeau, Katherine A.; Maldonado, Maria T. (Frontiers in Marine Science, 2016)
Microbial copper (Cu) nutrition and dissolved Cu speciation were surveyed along Line P, a coastal to open ocean transect that extends from the coast of British Columbia, Canada, to the high-nutrient-low-chlorophyll (HNLC) zone of the northeast subarctic Pacific Ocean. Steady-state size fractionated Cu uptake rates and Cu:C assimilation ratios were determined at in situ Cu concentrations and speciation using a 67Cu tracer method. The cellular Cu:C ratios that we measured (~30 µmol Cu mol C-1) are similar to recent estimates using synchrotron x-ray fluorescence (SXRF), suggesting that the 67Cu method can determine in situ metabolic Cu demands. We examined how environmental changes along the Line P transect influenced Cu metabolism in the sub-microplankton community. Cellular Cu:C assimilation ratios and uptake rates were compared with net primary productivity, bacterial abundance and productivity, total dissolved Cu, Cu speciation, and a suite of other chemical and biological parameters. Total dissolved Cu concentrations ([Cu]d) were within a narrow range (1.46 to 2.79 nM), and Cu was bound to a ~5-fold excess of strong ligands with conditional stability constants ( ) of ~1014. Free Cu2+ concentrations were low (pCu 14.4 to 15.1), and total and size fractionated net primary productivity (NPPV; µg C L-1 d-1) were negatively correlated with inorganic Cu concentrations ([Cu′]). We suggest this is due to greater Cu′ drawdown by faster growing phytoplankton populations. Using the relationship between [Cu′] drawdown and NPPV, we calculated a regional photosynthetic Cu:C drawdown export ratio between 1.5 and 15 µmol Cu mol C-1, and a mixed layer residence time (2.5 to 8 years) that is similar to other independent estimates (2-12 years). Total particulate Cu uptake rates were between 22 and 125 times faster than estimates of Cu export; this is possibly mediated by rapid cellular Cu uptake and efflux by phytoplankton and bacteria or the effects of grazers and bacterial remineralization on dissolved Cu. These results provide a more detailed understanding of the interactions between Cu speciation and microorganisms in seawater, and present evidence that marine phytoplankton modify Cu speciation in the open ocean.